Targeting PirAvp and PirBvp Toxins of Vibrio parahaemolyticus with Oilseed Peptides: An In Silico Approach - Joe-Hui Ong; Wey-Lim Wong; Fai-Chu Wong; Tsun-Thai Chai (MDPI AG, 2021)
Acute hepatopancreatic necrosis disease (AHPND), caused by PirAvp- and PirBvp-releasing Vibrio parahaemolyticus strains, has resulted in massive mortality in shrimp aquaculture. Excessive use of antibiotics for AHPND management has led to antibiotic resistance, highlighting the urgency to search for alternatives. Using an in silico approach, we aimed to discover PirAvp/PirBvp-binding peptides from oilseed meals as alternatives to antibiotics. To search for peptides that remain intact in the shrimp digestive tract, and therefore would be available for toxin binding, we focused on peptides released from tryptic hydrolysis of 37 major proteins from seeds of hemp, pumpkin, rape, sesame, and sunflower. This yielded 809 peptides. Further screening led to 24 peptides predicted as being non-toxic to shrimp, fish, and humans, with thermal stability and low water solubility. Molecular docking on the 24 peptides revealed six dual-target peptides capable of binding to key regions responsible for complex formation on both PirAvp and PirBvp. The peptides (ISYVVQGMGISGR, LTFVVHGHALMGK, QSLGVPPQLGNACNLDNLDVLQPTETIK, ISTINSQTLPILSQLR, PQFLVGASSILR, and VQVVNHMGQK) are 1139-2977 Da in mass and 10-28 residues in length. Such peptides are potential candidates for the future development of peptide-based anti-AHPND agents which potentially mitigate V. parahaemolyticus pathogenesis by intercepting PirAvp/PirBvp complex formation.